Impact of strategic information systems To achieve the agility of administrative processes (An applied study on government institutions in the Emirate of Fujairah) - AlDhanhani, Aishah (2021)
In light of the current situation in years 2020-2021 for the threat of the COVID-19 pandemic. The government organizations, see the importance of creating policies is to ensure the continuity of their work. The study will discuss the vision of the role played by strategic information systems (SIS) in enhancing the agility of administrative processes in government institutions in the Emirate of Fujairah. The study set three hypothesis to prove the SIS role and effect on the administrative processes according to different dimensions. Quantitative methods is used and the questionnaire tool is used to analyze the data. The results of the study can be summarized to, the study sample is aware of the SIS from its effects and not by its definition. Second result is the high positive relationship of the SIS characteristics to the agility of administrative processes. Third, the level of understanding the terms of SIS and agility in Fujairah government organizations is varies for variable (gender, years of experience, job position and academic qualification). The study finally presents recommendations for the results to improve Fujairah government organization.